Characterization of Health Status of Diabetic Population in the Area 2, Cienfuegos - Lister Garriga González; Midelsy Sánchez Nápoles; María de los Ángeles Vázquez Padrón (Revista Finlay)
Background: the most common site of infection among individuals hospitalized for diabetes is the foot; it is also a frequent cause of morbidity, mortality and disability. Objective: to characterize foot health of the diabetic population attending the podiatry consultation at the Health Area # 2 in Cienfuegos, from February to June 2013. Methods: A descriptive, cross-sectional study on the diabetic foot was conducted from February to June 2013. The study population consisted of 243 diabetic patients treated at the podiatry consultation and the sample matched the study population. The main variables used of the study were: age, sex, at-risk diabetic foot and complicated diabetic foot, level of risk and podiatric disorders diagnosed. Results: female patients attend consultation more frequently than males, accounting for 68.32 % and the ≥ 51 age group is most affected, with 138 patients. Among the 243 patients treated, 10 have a complicated diabetic foot, representing the 4.11 %. The rest of the patients (233) were identified as having at-risk foot (95.89 %); most of the patients are grouped in the third level of risk that includes lack of sensation or neuropathy. Conclusions: the most frequent podiatric disorders in the study population are: uncomplicated hyperkeratosis (195 cases), onychomycosis (159 cases), complicated hyperkeratosis (69 cases), onychogryphosis (34 cases), onicocriptosis and subungual hematoma, with a lower frequency, accounting for 9 and 7 cases respectively.